Spontaneous and atypical rhabdomyolysis in a collegiate tennis athlete - Fulcher, J. G.; Thompson, A. J (Journal of Athletic Training, 2019)
Background: A healthy 19 year old male tennis player participated in two tennis practices (am and pm) on the first day of pre-season (5.5 total hours). After practices, he and other teammates requested postactivity icebath immersion treatment. The patient exhibited no signs of heat illness prior to leaving the second practice. Upon ice immersion, the patient developed severe cramps in the lower extremity. Therapeutic interventions consisting of self and clinician-assisted stretching and massage were initiated along with fluid replacement. Attempts to alleviate cramping were unsuccessful. EMS was activated and the patient was transported to the emergency room (ER) for advanced medical care. Laboratory tests indicated a creatine kinase (CK) level of >8000 IU/L (normal range, 45-260 IU/L). Differential Diagnosis: Exertional heat cramps, dehydration, rhabdomyolysis. Treatment: The attending physician diagnosed the patient with rhabdomyolysis, admitted and treated the patient with intravenous fluids. The patient was prescribed with rest and rehydration and was released from the ER five days after admission. Blood tests were repeated throughout inpatient care and by eight days post incident, CK levels were within normal limits. Fourteen days after the initial incident, the patient described no other symptoms and was allowed to return to full tennis activities. Uniqueness: The patient demonstrated no signs of heat illness prior to leaving practice but experienced severe lower extremity cramping as he attempted icebath immersion, resulting in a diagnosis of exertional rhabdomyolysis. The patient showed no other signs of rhabdomyolysis other than elevated CK levels during inpatient care. Altered mental status was absent and heart rate and blood pressure were within normal limits. This is an atypical presentation of exertional rhabdomyolysis and may have been identified very early in the progression of the condition. It is suggested that further complications were prevented and permanent organ damage prevented. Conclusions: In this patient, CK levels appear to be a poor indicator of rhabdomyolysis. This patient demonstrated no other signs of heat illness during or after the incident, yet CK levels remained elevated for at least 5 days. Although the patient in this case showed no other signs of exertional rhabdomyolysis, the ability of clinicians to identify signs and symptoms of heat illness is critical in preventing the patients' condition from deteriorating and potentially causing permanent organ damage. Anticipatory detection of progressing signs and symptoms of heat illness promote timely diagnosis and facilitates earlier return to participation.